INFORMALITY IN GRANTED CREDITS AND ITS IMPACT ON TAX COMPLIANCE IN THE TRANSPORTATION SECTOR, 2010-2025 - Saldarriaga Sangama, Paolo José (2026)
This study analyzes the impact of informality in granted credits and its relationship with tax compliance in the Peruvian transportation sector during the 2010–2025 period. The research arises from the increasing use of non-regulated financing mechanisms and the difficulties faced by many companies in accessing the formal financial system. Methodologically, the study follows a quantitative approach, applied research type, non-experimental design, and a descriptive-correlational scope. The analysis was based on statistical and documentary information obtained from official sources related to financial inclusion, business informality,  and tax behavior. The findings reveal a gradual reduction in both informal financing and tax non-compliance throughout the study period. Likewise, a positive association between these variables was identified, suggesting that greater financial formalization could contribute to improved tax compliance levels within transportation-related activities.